Sulfur-Doped and Bio-Resin-Derived Hard Carbon@rGO Composites as Sustainable Anodes for Lithium-Ion Batteries - Huang, Qinyuan; Hu, Jinbo; Wen, Shujing; Zhang, Xiang; Liu, Gonggang; Chang, Shanshan; Liu, Yuan (Frontiers in Chemistry, 2020)
Hard carbon derived from fossil products is widely used as anode material for lithium-ion batteries. However, there are still several main shortcomings such as high cost, and poor rate performance, which restrict its wide application. Herein, we report the sulfur-doped hard carbon (SHC) materials derived from the biomass tannin-furanic resins (TF-Resin), followed by enveloping rGO on its surface through the hexadecyl trimethyl ammonium bromide. SHC provides sites for the storage of lithium, while the rGO layers can offer a highly conductive matrix to achieve good contact between particles and promote the diffusion and transport of ions and electrons. As a result, the SHC@rGO shows excellent lithium storage performance with initial discharge capacity around 746 mAh g-1 at a current density of 50 mAg-1 and shows superb stability keeping capacity retention of 91.9% after 200 cycles. Moreover, even at a high current density of 2000 mAg-1, SHC@rGO still delivers a specific capacity of 188 mAg-1. These desired promising properties are believed to implement in practical application.